Type-specific HPV prevalence in invasive cervical cancer in the UK prior to national HPV immunisation programme: baseline for monitoring the effects of immunisation. Issue 2 (19th November 2014) - Mesher, David; Cuschieri, Kate; Hibbitts, Sam; Jamison, Jackie; Sargent, Alex; Pollock, Kevin G; Powell, Ned; Wilson, Robbie; McCall, Fiona; Fiander, Alison; Soldan, Kate
Abstract : Aims: To establish the human papillomavirus (HPV) type-specific prevalence in cervical cancer and high-grade cervical lesions in the UK prior to the introduction of national HPV vaccination. Methods: Specimens of cervical cancer (n=1235) and cervical intraepithelial neoplasia (CIN)3 (n=2268) were tested for HPV genotypes in England, Scotland, Wales and Northern Ireland. Data were pooled and weighted estimates presented. Results: Among cervical cancer cases, 95.8% were positive for at least one high-risk (HR) HPV type. Restricting to those with HR HPV, the proportion positive for HPV16 and/or HPV18 was similar across countries (weighted overall prevalence 83.0%). This proportion decreased with increasing age at diagnosis (p=0.0005). HPV31, HPV33, HPV45, HPV52 and/or HPV58 were detected in 16.1% of HR HPV-positive cervical cancers and there was no significant association with age for these types. For HR HPV-positive CIN3 cases, there was a similar age-specific pattern with the highest positivity of HPV16 and/or HPV18 in the youngest age group (77.2%). The proportion of HR HPV CIN3 cases positive for HPV31, HPV33, HPV45, HPV52 and/or HPV58 was 36.3% in those aged <30 years at diagnosis. Conclusions: The prevalence of HPV 16 and/or 18 was high in all UK countries and highest in those diagnosed at a younger age. The UK is well placed to monitor the impact of HPV vaccination on type-specific HPV prevalence in cervical disease.